A Sorry Excuse for an Apology: Examining People's Mental Representations of an Apologetic Face. - George, Meghan; Guilfoyle, Joshua R.; Steele, Jennifer R.; Struthers, C. W. (Journal of Nonverbal Behavior, 2023)
The goal of the current research was to gain an understanding of people's mental representations of an apologetic face. In Study 1, participants' responses were used to generate visual templates of apologetic faces through reverse correlation (Study 1a, n = 121), and a new set of participants (Study 1b, n = 37 and 1c, n = 153) rated that image (group-level Classification Image, CI), as well as either the inverse image (group-level anti-CI in Study 1b) or base face (in Study 1c), on apology-related characteristics. Results demonstrated that people have a mental representation of an apologetic face, and that sadness is an important feature of this template. To examine similarities between mental representations of apologetic and sad faces, participants in Study 2 generated visual templates of sad faces using reverse correlation (Study 2a, n = 121). New participants (Study 2b, n = 162) were then randomly assigned to rate the averaged face, eyes, and mouths (group-level CIs) as well as the individual visual templates (individual-level CIs) generated from both studies for either how apologetic or sad they appeared. Visual templates of apologetic and sad faces were seen as apologetic, providing evidence of the prominence of sadness in mental representations of apology.